Agricultural Extension Approaches and Rural Youth Engagement in West Bengal: A Comprehensive Review - Ghosh, Swapnamay; Sarkar, Atreyee; Chakraborty, Saumyadip; Mondal, Krishnendu; Malitha, Ainul Bari (NG Agricultural Sciences, 2025)
The ageing farm population and rising rural–urban migration threatens the sustainability of India’s agrarian economy. Rural youth are vital for rejuvenating agriculture, yet they increasingly perceive farming as a low-status occupation and seek alternative livelihoods. West Bengal, home to over 9 million rural youths, provides a unique laboratory for analysing how extension systems can engage young people in agriculture. This review synthesises literature published between 2005 and 2025 to examine the evolution of agricultural extension approaches in West Bengal, the role of extension in youth skill development and employment, digital extension innovations, agripreneurship promotion, and institutional and policy support for rural youth. A conceptual framework anchored in the Agricultural Knowledge and Innovation System (AKIS), youth engagement theory, diffusion of innovations and human capital and sustainable livelihood frameworks guides the analysis. The findings reveal that West Bengal’s extension system has transitioned from top-down public advisory to pluralistic and market-oriented services, with Krishi Vigyan Kendras (KVKs), Agricultural Technology Management Agency (ATMA) platforms, corporate and non-governmental organisations (NGOs) playing key roles. Programmes such as Attracting and Retaining Youth in Agriculture (ARYA), Skill Training for Rural Youth (STRY), Agri Clinic and Agri Business Centre (ACABC) and Diploma in Agricultural Extension Services for Input Dealers (DAESI) have fostered technical competence, employment and entrepreneurship. Digital tools—mobile phones, internet advisories and platforms like BigHaat and telecentres—enhanced knowledge access. Social enterprises and incubators such as ONganic Foods and Green College illustrate how social–ecological models can create livelihood opportunities and preserve ecological values. The review concludes with policy and research recommendations for strengthening youth centred extension by integrating inclusive digital platforms, tailoring training to differentiated youth typologies, supporting collective enterprises, and forging cross sectoral partnerships to build resilient and sustainable agricultural livelihoods.